2017
DOI: 10.2169/internalmedicine.56.7808
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of Behçet's Disease Associated with Acute Myeloid Leukemia with Myelodysplasia-related Changes Using Azacitidine and Tacrolimus before Allogeneic Hematopoietic Stem Cell Transplantation

Abstract: The coexistence of acute myeloid leukemia (AML) with Behçet's disease (BD) is rare. The optimum treatment for AML-associated BD has not been established. We herein report a patient with BD who developed AML with myelodysplasia-related changes. Induction chemotherapy caused complete remission of the AML but worsened the BD. Thereafter, AML was treated with azacitidine. The BD was steroid-dependent. Tacrolimus was added, which improved the BD. The patient underwent allogeneic hematopoietic stem cell transplantat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 16 publications
(18 reference statements)
0
6
0
Order By: Relevance
“…(187) There have been rare case reports of BD associated with MDS, (188,189) CML-chronic phase, (190,191) and AML. (192,193) Cytogenetic aberrations, especially trisomy 8 which occurs in 64-87% of BD-MDS cases, (194,195) are thought to play an important role in the pathogenesis of BD associated with MDS. In a population-based study, by Jung et al, (196) patients with BD had a greater risk of MDS than the general population (SIR 65.7 [7.9-237.4] in men and 53.9 [11.1-157.4] in women), but not of hematological cancer.…”
Section: Glomerulonephritides and Myeloid Neoplasmsmentioning
confidence: 99%
See 1 more Smart Citation
“…(187) There have been rare case reports of BD associated with MDS, (188,189) CML-chronic phase, (190,191) and AML. (192,193) Cytogenetic aberrations, especially trisomy 8 which occurs in 64-87% of BD-MDS cases, (194,195) are thought to play an important role in the pathogenesis of BD associated with MDS. In a population-based study, by Jung et al, (196) patients with BD had a greater risk of MDS than the general population (SIR 65.7 [7.9-237.4] in men and 53.9 [11.1-157.4] in women), but not of hematological cancer.…”
Section: Glomerulonephritides and Myeloid Neoplasmsmentioning
confidence: 99%
“…In regard to management of these patients, several of the cases in the aforementioned reports were treated with allogeneic stem cell transplantation which resulted in the resolution of remission of MDS/AML and BD. (188,189,192,193) Sjogren's syndrome and myeloid neoplasms: Sjogren's syndrome (SS) is an inflammatory disorder most often affecting the tear and salivary glands, and may either be primary or secondary (prior rheumatologic disease such as SLE or RA) in origin. Although an association between SS and myeloid malignancies is extremely rare, cases of AML, (197) CML, (198) and CMML (199) have been described, either as a paraneoplastic syndrome or in the context of prior cyclophosphamide exposure.…”
Section: Glomerulonephritides and Myeloid Neoplasmsmentioning
confidence: 99%
“…Several reports have highlighted the potential efficacy of azacytidine [3] , but its clinical evaluation has yet to be determined. Allo-HSCT has been reported to control both MDS and BLD in some cases [3] , [4] , [5] , [6] , [7] , [8] . However, there have been limited reports of complications related to allo-HSCT for MDS with BLD.…”
Section: Introductionmentioning
confidence: 99%
“…Among hematological malignancies, chronic myeloid leukemia and lymphoma have been reported in patients with BD [8]. In only a few cases has acute myeloid leukemia been found in patients with Behçet’s disease [911]. A large study on 651 patients with BD showed that malignancy occurred in 6.3% of the patients [9].…”
Section: Discussionmentioning
confidence: 99%
“…Hematopoietic stem cell transplant (HSCT) is considered curative for acute myeloid leukemia. HSCT has also been shown to be very effective in inducing remission in Behçet’s disease [11, 16].…”
Section: Discussionmentioning
confidence: 99%